Measuring the Effect of Bankruptcy Laws on Entrepreneurship Across Countries - Douglas J. Cumming (The Journal of Entrepreneurial Finance (JEF), 2012)
Two recent papers examine the impact of corporate bankruptcy laws on new business start-ups in 29 countries over 1990 - 2008 (Peng et al., 2010; Lee et al., 2010). In this commentary, I briefly point out two significant issues which future researchers might want to consider. First, several countries in the data examined had changed their personal and corporate bankruptcy laws over the years studied. It is statistically inappropriate and inaccurate to treat bankruptcy laws as time invariant, as in Peng et al. (2010) and Lee et al. (2010), particularly in view of the dramatic changes in bankruptcy laws over time in so many countries. Second, Peng et al. (2010) and Lee et al. (2010) have a misplaced focus on corporate bankruptcy law while ignoring personal bankruptcy law. This focus is at odds with theory and prior work on topic which relates entrepreneurship to personal bankruptcy law.
Keywords: G33; G38; K22; M13; 650; Bankruptcy; Bankruptcy Law; Entrepreneurship